PENGARUH KEPEMIMPINAN DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PT LIMA SEMPURNA CIKANDE â SERANG - Syamsudin, Syamsudin (Sains Manajemen, 2016)
This study aims to determine how much influence the leadership on performance of employess, to determine how much influence the compensationon performance of employess, to determine how much influence the leadership and compensation on performance of employess PT. Lima sempurna Cikande - Serang.The method in this study using quantitative research methods, can be interpreted as a method of research that is based on the philosophy of positivism, is used to examine the population or a particular sample, data collection techniques using research instruments, analysis of quantitative data/statistics with the aim to test the hypothesis that has been set, The population in this research were 32 respondents at PT. Lima sempurna Cikande â Serang.Based on research that has been done, the conclusion is a significant difference between the leadership on performance of employess obtained t hitung > t table ( (3,344> 2,045 ) with a significant level of ( 0,02 < 0,05) . Scale measurements on each item questionnaire leadership variable (X 1 ) then obtained an assessment of the questionnaire items of wholly obtained average value ofÂ  137,9 with a measurement scale on a scale of 136-162 in the âvery goodâcategory. There is a significant difference between the compensation on performance of employess, obtained t hitung > t table ( 5,688 > 2,045 ) with asignificant level of ( 0,00< 0,05 ) Scale measurements on each item questionnaire compensation variable (X 2 ) the obtained assessment of the questionnaire items of wholly obtained average value of 135,9Â  with a measurement scale on a scale of 110-136 in the âgoodâ category. There is a significantrelationship between the leadership and and compensation on performance of employess F hitung > F table ( 15,678 > 2,93 ).with a significant level of ( 0,00< 0,05 ). Scale measurements on each item on the questionnaire variables performance of employess (Y), then obtained an assessment of the questionnaire items of wholly obtained average value ofÂ  136,4 with a measurement scale on a scale of 136-162 in the âVery goodâcategories.